Effect of brivaracetam (400 mg/day) on the pharmacokinetics and pharmacodynamics of a combination oral contraceptive in healthy women. (10th October 2013) - Stockis, Armel; Rolan, Paul
Abstract Brivaracetam is a high‐affinity synaptic vesicle protein 2A ligand, in Phase III clinical development for epilepsy. This study assessed the effect of brivaracetam 400 mg/day on the pharmacokinetics and pharmacodynamics of a combination oral contraceptive (OC) containing 30 µg ethinylestradiol and 150 µg levonorgestrel, in healthy pre‐menopausal women. This open‐label, single‐center, randomized, two‐way crossover, multiple oral dose study (N01080) included two consecutive 28‐day cycles without (control) or with brivaracetam (test), and a 28‐day follow‐up. OC was taken on Days 1–21 of every cycle and brivaracetam 200 mg twice daily was administered on Days 1–20 of the test cycle. Ethinylestradiol and levonorgestrel pharmacokinetics were determined on Day 20 and endogenous hormones were measured frequently during both control and test cycles. Overall, 23/24 participants (age: 19–39 years) completed the study. AUC ratio (90% confidence interval) for brivaracetam versus control was 0.73 (0.69, 0.78) for ethinylestradiol and 0.78 (0.72, 0.83) for levonorgestrel, outside pre‐defined bioequivalence limits (0.80–1.25). Levels of endogenous hormones were similar and normal during brivaracetam and control cycles. Brivaracetam in combination with OC was well tolerated. Brivaracetam 400 mg/day co‐administered with a combination OC in healthy women reduced ethinylestradiol and levonorgestrel plasma levels but did not result in ovulation.